Edaravone Plays Protective Effects on LPS-Induced Microglia by Switching M1/M2 Phenotypes and Regulating NLRP3 Inflammasome Activation - Li, Jiping; Dai, Xinping; zhou, Liuyi; Li, Xinxiu; Pan, Dongxiao (Frontiers in Pharmacology, 2021)
Parkinson's disease is a neurodegenerative disorder in which activated microglia may appear prior to motor symptoms, but the specific therapeutic mechanisms remain unclear. This study investigated the potential effects of Edaravone (EDA) on M1/M2 polarization of microglia in rats with dopaminergic neurons damage induced by lipopolysaccharide (LPS) and its mechanism. Rats were randomly grouped as the following (n=10): Control, EDA alone (10 mg/kg), LPS-model (LPS 5 μg), LPS+EDA (5 mg/kg) and LPS+EDA (10 mg/kg). After intragastric administration of EDA once a day for 7 consecutive days, LPS was injected into SN pars unilaterally. Rotarod test, pole test, and traction test were used to analyze the intervention effect of EDA on neurobehavioral function in rats. Protein expression levels of TH, TNF-α, Arg-1, Iba-1, NLRP3 and caspase-1 were measured by immunofluorescence staining and western blot. In vitro, BV-2 cells were treated with LPS (100 ng/ml) before adding different doses of EDA. Levels of inflammatory cytokines in culture medium were detected by ELISA. Western blot and immunofluorescence were used to evaluate microglial activation and polarization. First, rotarod test, pole test, and traction test all showed that EDA mitigated motor dysfunction of PD rats. Second, pathological analysis suggested that EDA inhibited LPS-induced microglial activation and remitted declines of dopaminergic neurons. In addition, EDA shifted M1 pro-inflammatory phenotype of microglia to M2 anti-inflammatory state, while decreased expression of M1 markers (TNF-α and IL-1β) and facilitated expression of M2 markers (Arg-1 and IL-10). EDA suppressed inflammatory responses through inhibiting the expression of pro-inflammatory factors (IL-1β, IL-18 and NO), but the neuroprotective effects were invalid while siRNA NLRP3 existed. In conclusion, these results indicated that EDA could improve neurobehavioral functions and play anti-neuroinflammatory roles in PD rats, possibly by inhibiting NLPR3 inflammasome activation and regulating microglia M1/M2 polarization.